Mental Health in Schools : Engaging Learners, Preventing Problems, and Improving Schools. - Adelman, Howard S. (SAGE Publications, 2009)
""This book is a must-read for those seeking support in creating meaningful school improvement plans and valuable, comprehensive healthy school initiatives."